Case studies in fluid mechanics with sensitivities to governing variables - Atesmen, M. Kemal (The Wiley-ASME Press series in mechanical engineering, 2019)
"Covers a wide range of practical fluid mechanics, heat transfer, and mass transfer problems - Examines the basic laws of fluid mechanics, heat transfer and mass transfer - Each problem solution starts with simplifying engineering assumptions and identifies the governing equations and dependent and independent variables - Presents solutions to governing equations with experimental studies Market description: Tier 3/ P & R Primary: Practicing engineers working in thermo-physical sciences. Secondary: Graduate students in mechanical engineering"--